Some implications of tax reform - De Buitleir, D. (Statistical and Social Inquiry Society of Ireland, 1984)
The present Irish tax system is conceded on all sides to be totally unsatisfactory. It is unfair and complicated. It wastes resources on a grand scale. Reform is long overdue. In this paper I examine the changes in the burden of taxation in recent years and discuss how the proposals for tax reform proposed by the Commissionon Taxation can begin to be implemented.
Symposium on Taxation
Read before the Society, 2nd November, 1983
Keywords: Tax reform; Income tax; Tax base; Real income; 314.15